New Approaches to Overcome Transport Related Drug Resistance in Trypanosomatid Parasites - Garcia-Salcedo, Jose A.; Unciti-Broceta, Juan D.; Valverde-Pozo, Javier; Soriano, Miguel (Frontiers in Pharmacology, 2016)
Leishmania and Trypanosoma are members of the Trypanosomatidae family that cause severe human infections such as leishmaniasis, Chagas disease, and sleeping sickness affecting millions of people worldwide. Despite efforts to eradicate them, migrations are expanding these infections to developing countries. There are no vaccines available and current treatments depend only on chemotherapy. Drug resistance is a major obstacle for the treatment of these diseases given that existing drugs are old and limited, with some having severe side effects. Most resistance mechanisms developed by these parasites are related with a decreased uptake or increased efflux of the drug due to mutations or altered expression of membrane transporters. Different new approaches have been elaborated that can overcome these mechanisms of resistance including the use of inhibitors of efflux pumps and drug carriers for both active and passive targeting. Here we review new formulations that have been successfully applied to circumvent resistance related to drug transporters, opening alternative ways to solve drug resistance in protozoan parasitic diseases.